2016
DOI: 10.7475/kjan.2016.28.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Management, Beliefs, and Competence on Evidence-Based Practice, Evidence-Based Decision Making of Nurses in General Hospitals

Abstract: Purpose:The purpose of this study was to explore how knowledge management of hospital and nurses' beliefs and competences on evidence-based practice can affect evidence-based decision making. Methods: In this descriptive study, a total of 184 nurses who were working in the five general hospitals participated. The data were collected through a self-administered questionnaire in September, 2014. Data were analyzed using descriptive statistics, independent t-test, one-way ANOVA, Pearson correlation coefficient, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Possible total scores range from 16 to 80 points, with higher scores indicating positive EBP beliefs. At the time of its development, the Cronbach’s alpha of the tool was 0.90 [36] and 0.88 for Korean nurses [34]. In this study, the Cronbach’s alpha was found to be 0.81.…”
Section: Methodsmentioning
confidence: 71%
See 3 more Smart Citations
“…Possible total scores range from 16 to 80 points, with higher scores indicating positive EBP beliefs. At the time of its development, the Cronbach’s alpha of the tool was 0.90 [36] and 0.88 for Korean nurses [34]. In this study, the Cronbach’s alpha was found to be 0.81.…”
Section: Methodsmentioning
confidence: 71%
“…EBP experts emphasize that nurses should be sensitive to the continuously generated scientific knowledge and have sufficient knowledge to make critical judgments about such research in order to perform EBP [12, 15, 24, 25]. However, EBP knowledge is difficult to improve by nurses' personal efforts alone, so organizational support is needed [34]. Several previous studies suggest the necessity of learning atmospheres and facilities for successful EBP establishment in nursing organizations [12, 21, 38, 39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the communication (沟通) terminology in the original NHS SM item two was challenging to match in Chinese in that context because, according to the Xinhua dictionary, "communicate" in Chinese means to make both parties understand each other, such as ideas, culture [ 37 ], yet “communication” in NHS SM means much more than just two parties. It took four rounds of group discussion and confirmation with the author of NHS SM before we finally settled on translating it into “dissemination” (传播), which is the process of transmitting information, intelligence, opinions, feelings and directly or indirectly between people or groups of people with the help of verbal and non-verbal symbols in Chinese [ 38 ].…”
Section: Discussionmentioning
confidence: 99%